The 1998 Ice Storm: Local flow fields and linkages to precipitation - Henson, William; Stewart, Ronald; Kochtubajda, Bohdan; Thériault, Julie (Atmospheric Research, 2011)

A Numerical Study of the June 2013 Flood-Producing Extreme Rainstorm over Southern Alberta - Li, Yanping; Szeto, Kit; Stewart, Ronald E.; Thériault, Julie M.; Chen, Liang; Kochtubajda, Bohdan; Liu, Anthony; Boodoo, Sudesh; Goodson, Ron; Mooney, Curtis; Kurkute, Sopan (Journal of Hydrometeorology, 2017)
Abstract A devastating, flood-producing rainstorm occurred over southern Alberta, Canada, from 19 to 22 June 2013. The long-lived, heavy rainfall event was a result of complex interplays between topographic, synoptic, and convective processes that rendered an accurate simulation of this event a challenging task. In this study, the Weather Research and Forecasting (WRF) Model was used to simulate this event and was validated against several observation datasets. Both the timing and location of the model precipitation agree closely with the observations, indicating that the WRF Model is capable of reproducing this type of severe event. Sensitivity tests with different microphysics schemes were conducted and evaluated using equitable threat and bias frequency scores. The WRF double-moment 6-class microphysics scheme (WDM6) generally performed better when compared with other schemes. The application of a conventional convective/stratiform separation algorithm shows that convective activity was dominant during the early stages, then evolved into predominantly stratiform precipitation later in the event. The HYSPLIT back-trajectory analysis and regional water budget assessments using WRF simulation output suggest that the moisture for the precipitation was mainly from recycling antecedent soil moisture through evaporation and evapotranspiration over the Canadian Prairies and the U.S. Great Plains. This analysis also shows that a small fraction of the moisture can be traced back to the northeastern Pacific, and direct uptake from the Gulf of Mexico was not a significant source in this event.

A Review and Synthesis of Future Earth System Change in theInterior of Western Canada: Part I – Climate and Meteorology - Stewart, Ronald E.; Szeto, Kit K.; Bonsal, Barrie R.; Hanesiak, John M.; Kochtubajda, Bohdan; Li, Yanping; Thériault, Julie M.; DeBeer, Chris M.; Tam, Benita Y.; Li, Zhenhua; Liu, Zhuo; Bruneau, Jennifer A.; et al. (Hydrometeorology/Modelling approaches, 2019)
Abstract. The Interior of Western Canada, up to and including the Arctic, has experienced rapid change in its climate, hydrology, cryosphere and ecosystems and this is expected to continue. Although there is general consensus that warming will occur in the future, many critical issues remain. In this first of two articles, attention is placed on atmospheric-related issues that range from large scales down to individual precipitation events. Each of these is considered in terms of expected change organized by season and utilizing climate scenario information as well as thermodynamically-driven future climatic forcing simulations. Large scale atmospheric circulations affecting this region are generally projected to become stronger in each season and, coupled with warming temperatures, lead to enhancements of numerous water-related and temperature-related extremes. These include winter snowstorms, freezing rain, drought as well as atmospheric forcing of spring floods although not necessarily summer convection. Collective insights of these atmospheric findings are summarized in a consistent, connected physical framework.